2020
DOI: 10.3748/wjg.v26.i20.2669
|View full text |Cite
|
Sign up to set email alerts
|

Association between non-alcoholic fatty liver disease and obstructive sleep apnea

Abstract: Author contributions: Umbro I wrote the paper; Umbro I and Fabiani V collected and analyzed data; Umbro I, Fabiani V, Fabiani M, Angelico F and Del Ben M designed the study, critically reviewed and approved the final version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 52 publications
(46 reference statements)
0
28
0
Order By: Relevance
“…[ 1 ] The chronic intermittent nocturnal hypoxia resulting from repeated upper airway obstruction in OSA patients is considered to be a contributing factor in the development of NAFLD. [ 2 ] The general population prevalence estimates for OSA vary from 9.3% in India[ 3 ] to that of around 24% and 9% in male and females, respectively, from USA. [ 4 ] For ≥5 AHI events, the overall population prevalence is estimated to vary from 9% to 38%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] The chronic intermittent nocturnal hypoxia resulting from repeated upper airway obstruction in OSA patients is considered to be a contributing factor in the development of NAFLD. [ 2 ] The general population prevalence estimates for OSA vary from 9.3% in India[ 3 ] to that of around 24% and 9% in male and females, respectively, from USA. [ 4 ] For ≥5 AHI events, the overall population prevalence is estimated to vary from 9% to 38%.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] NAFLD is an emerging liver disease and currently the most common cause of incidental abnormal liver tests. [ 2 ] The worldwide prevalence of NAFLD is estimated to be around 25% in general population and in up to 75% in obese individuals. [ 6 7 ] In patients undergoing bariatric surgery and having OSA, NAFLD is present in around 80% of cases and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Of the several sleep disorders, obstructive sleep apnoea and short sleep duration have been established as risk factors for NAFLD. [6][7][8][9][10][11] On the other hand, only a few reports of the association between sleep quality and NAFLD have been published. 9 12 13 The Pittsburgh Sleep Quality Index (PSQI) is an established and widely used method for sleep quality evaluation; it comprises seven elements, including subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbance, sleep medication use and daytime dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…OSA has been shown to be correlated with the presence of NAFLD and severity of NAFLD, including lobular inflammation, ballooning degeneration, and fibrosis [ 118 - 120 ]. A recent study demonstrated an increased prevalence of NAFLD in patients with OSA, even in the absence of obesity or metabolic syndrome [ 120 ]. The data on the association between OSA and fibrosis are mixed.…”
Section: Obstructive Sleep Apnea (Osa)mentioning
confidence: 99%